Aldehyde-Low Endothelial Progenitor Cells in Ischemic Wound Repair, Regulated by SDF1/CXCR4 - Dias Rima Sutiono; Candra Louis (PT. Kalbe Farma Tbk., 2018)
The incidence rate of both ischemic heart disease and ischemic stroke over the past decade has become a concern in the respect of global mortality rate. Ischemia is a condition of oxygen deprivation in the specific tissue which leads to loss of organ function. Regenerative medicine by using the endothelial progenitor cells (EPCs) show a great potential, especially the Alde-Low EPCs. The Alde-Low EPCs are regulated mainly by the chemo-attractant proteins of SDF1/CXCR4 which responsible for the cell migration and is regulated by the HIF2α. Further investigation and research on the correlation of SDF1/CXCR4 and the Alde-Low EPCs are needed.Iskemi merupakan suatu kondisi pengambilan oksigen pada spesifik jaringan yang memicu kehilangan fungsi organ. Peningkatan kejadian dan kematian akibat penyakit jantung Ikemik dan stroke iskemik secara global pada beberapa dasawarsa telah menjadi perhatian. Upaya regenerasi menggunakan sel progenitor endothelial (EPCs) memperlihatkan potensi sangat tinggi, khususnya Alde- rendah EPCs. Alde-rendah EPCs diregulasi oleh protein chemoattractant dari SDF1/CXCR4 yang bertanggung jawab untuk migrasi sel dan diregulasikan oleh HIF2α. Hubungan SDF1/CXCR4 dan Alde-rendah EPCs masih perlu diteliti lebih lanjut.